A HUMAN RIGHTS APPROACH TO LIABILITY FOR SPACE DAMAGE - Semchuk, Natalia (Proceedings of National Aviation University (archive), 2019)
The purpose of the research: to identify the areas of optimization of legal regulation of liability for space damage on the basis of a comprehensive analysis of international acts and legislation of foreign countries. Methods of research: To achieve the purpose of the study were used general and specific scientific (special). Among the latter, particular attention is paid to the use of the system approach and the comparative method. Results: At present, there are no studies in the Ukrainian legislation and legal science aimed at the comprehensive study of the issues of space law in the context of human rights. That is, the problem of the relationship between space law and human rights in the Ukrainian context is still not sufficiently investigated. However, for Ukraine, which is a "launching state" in the sense of international law, this issue is relevant. The study is one of the first attempts to study the issues of space law in the context of human rights, especially environmental ones. Therefore, the article focuses on the international legal aspects of liability for damage to human ecological rights, which can be caused by space objects. Discussion: The authors offer ways to optimize the legal regulation of liability for damage to human ecological rights, which can be caused by space objects and emphasize the peculiarities of responsibility "launching countries" in the context of protecting environmental human rights.